Biochar and Water Quality. Issue 1 (1st January 2019) - Blanco‐Canqui, Humberto
Abstract : Biochar application is considered to be an emerging strategy to improve soil ecosystem services. However, implications of such application on water quality parameters have not been widely discussed. This paper synthesizes the state‐of‐the‐art research on biochar effects on water erosion, nitrate leaching, and other sources of water pollution. Literature indicates that in general, biochar application reduces runoff by 5 to 50% and soil loss by 11 to 78%, suggesting that it can be effective at reducing water erosion, but the magnitude of erosion reduction is highly variable. Co‐application of biochar with other organic amendments (i.e., animal manure, compost) appears to be more effective at reducing water erosion than biochar alone. A main mechanism by which biochar can reduce water erosion is by improving soil properties (i.e., organic C, hydraulic conductivity, aggregate stability), which affect soil erodibility. This review also indicates that biochar reduces nitrate leaching, in most cases by 2 to 88%, but has mixed effect on phosphate and dissolved C leaching. Additionally, biochar effectively filters urban runoff, adsorbs pollutants, and reduces pesticides losses. Biochar feedstock, pyrolysis temperature, application amount, time after application, and co‐application with other amendments affect biochar impacts on water quality. Biochar erosion and potential reduction in nutrient and pesticide use efficiency due to the strong adsorption are concerns that deserve consideration. Overall, biochar application has the potential to reduce water erosion, nitrate leaching, pesticide losses, and other pollutant losses, but more field‐scale data are needed to better discern the extent to which biochar can improve water quality. Core Ideas: Biochar can reduce water erosion, but the magnitude of reduction is variable. Biochar combined with other organic amendments can reduce water erosion more than biochar alone. Biochar can reduce nitrate leaching but has mixed effects on phosphate and dissolved C leaching. Biochar filters urban runoff, adsorbs organic pollutants, and reduces pesticide losses. More field data on the effectiveness of biochar for improving water quality are needed.